1998
DOI: 10.1128/mcb.18.7.4157
|View full text |Cite
|
Sign up to set email alerts
|

The C-Terminal Domain of Sin1 Interacts with the SWI-SNF Complex in Yeast

Abstract: In the yeast Saccharomyces cerevisiae, the SWI-SNF complex has been proposed to antagonize the repressive effects of chromatin by disrupting nucleosomes. The SIN genes were identified as suppressors of defects in the SWI-SNF complex, and the SIN1 gene encodes an HMG1-like protein that has been proposed to be a component of chromatin. Specific mutations (sin mutations) in both histone H3 and H4 genes produce the same phenotypic effects as do mutations in the SIN1 gene. In this study, we demonstrate that Sin1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
21
1
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 55 publications
3
21
1
1
Order By: Relevance
“…That interpretation is consistent with another observation that overexpression of the C-terminal of Sin1p (where the sin1-2 mutation is found) is toxic (8), but that this toxicity is suppressed in spt4, spt5, and spt6 strains. Each of these proteins, like Hpr1p, has been implicated in modification of chromatin structure.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…That interpretation is consistent with another observation that overexpression of the C-terminal of Sin1p (where the sin1-2 mutation is found) is toxic (8), but that this toxicity is suppressed in spt4, spt5, and spt6 strains. Each of these proteins, like Hpr1p, has been implicated in modification of chromatin structure.…”
Section: Discussionsupporting
confidence: 91%
“…Later, Perez-Martin and Johnson (8) showed that the C terminus of Sin1p physically associates with components of the SWI͞SNF complex and that this interaction is blocked in the full-length Sin1p protein by the Nterminal half of the protein. Recently, it has been reported that SWI͞SNF can stimulate transcription even after promoter clearance (34) during elongation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when we examined GAL10-MEL1 expression in a yeast strain carrying the hhf2-13 mutation in histone H4, we did not see any increase in stimulation by GAL4-TBP (Ryan and Morse, unpublished). Thus, although this sin mutation alleviates the requirement for SWI-SNF for transcriptional activation of an HO-lacZ reporter gene (58,75) and increases accessibility of nucleosomal DNA to MNase and Escherichia coli Dam methyltransferase in yeast (75), it evidently does not sufficiently perturb the local chromatin structure of the GAL10 promoter to allow activation by GAL4-TBP. We also employed an altered GAL10-MEL1 reporter having a LexA binding site between the GAL4 binding sites and the TATA element to ask whether artificial depletion of histone H4 would allow activation by LexATBP.…”
Section: Discussionmentioning
confidence: 94%
“…The prototype of this remodeling machine is the evolutionary conserved human SWI/SNF, a multisubunit complex composed of Brm and Brg1 subunits (62,63). Recent, experimental data showed that these constituents are associated with transcriptional repressors like Sin (46,53). Chromatin remodeling by Mi-2, a member of the SWI/SNF superfamily, has also been purified with HDAC activity and shown to repress transcription in a methylation-dependent manner (59).…”
Section: Discussionmentioning
confidence: 99%